Giant Steppes: Protecting Mongolia's Grasslands in the Face of a Mining Boom - Joshua Zaffos (Symphony in the Flint Hills, 2015)
Amar Purev, a square-jawed preserve ranger with a no-nonsense demeanor, peers through binoculars from the window of an SUV as it bounces along a double-track path through a green-and-golden sea of hip-high grass. He spots only a few gazelles in the distance, but when the vehicle crests a hill, it halts: fifty yards away, hundreds of gazelles and their calves graze on stipa, or feather grass. Before Purev can open his door, the animals take off, coursing 40 miles per hour across the flat and boundless expanse that reaches to the horizon. This grassy ocean is Mongolia’s Toson Hulstai Nature Reserve, a protected area of more than 1 million acres. It is part of a 68 million-acre expanse of grasslands that stretch from forests to desert across the country’s Eastern Steppe.
Keywords: mining; government; threat; grassland; grass; prairie; Asia; herders; way of life; every day; protection; protect; save; importance; animals; native; nature; peoples; farming; urbanization; industrialization; nomads; nomadic; travel; hike